AI-Driven Economies: How Artificial Intelligence (AI) is Reshaping Business Administration and Decision-Making. - Butt, Junaid (Acta Universitatis Danubius. Œconomica, 2024)
In an era where artificial intelligence (AI) is no longer a futuristic concept but a transformative force in business, this article explores the profound impact of AI on business administration and decision-making. On March 13, 2024, the European Union (EU) Parliament adopted the world”s first law governing "artificial inelegance" the EU Artificial Intelligence Act of 2024 “the EU AI Act, 2024”. As organizations increasingly embrace AI technologies, they are not only enhancing operational efficiency but also reimagining their business models and strategies. This research delves into the ways AI is revolutionizing traditional practices, from automating routine tasks to facilitating data-driven insights that drive strategic innovation. Through compelling case studies across various industries, we highlight the successes and challenges faced by companies navigating this AI-driven landscape. Additionally, we examine the implications for the workforce, addressing concerns over job displacement and the urgent need for reskilling in an increasingly automated world. By analyzing emerging trends and projecting the long-term effects of AI on global business ecosystems, this article provides a comprehensive overview of how AI is reshaping the future of work, competition, and economic growth. Join us as we uncover the opportunities and risks presented by AI-driven economies and chart a path toward a sustainable and inclusive business landscape.